Tantangan Hukum dan Perlindungan Hak Anak: Analisis Perkawinan Anak di Bawah Umur - Budi Setiawan (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Child marriage is a serious problem that requires serious attention from various parties, including the government, non-governmental organizations, civil society and families. This research method uses a qualitative method with an interdisciplinary approach. This research aims to analyze the factors that cause child marriage and the challenges in protecting and upholding children's human rights as an integrated part of human rights, through social, cultural and economic perspectives that are interconnected with the applicable legal framework. The research results show that child marriage is still widespread due to various social, cultural and economic factors. Even though there are regulations that set a minimum age limit for marriage, this practice still continues, and has a negative impact on children's development, especially in terms of education and health. Educating the public about the negative consequences of child marriage, strengthening legal regulations that prohibit this practice, as well as supporting reproductive health services, education and social assistance for children and their families are important in prevention. Synergy between institutions such as the government, police, child protection agencies and non-governmental organizations is also needed to strengthen law enforcement.